Cytomorphological characteristics evaluation of the third generation of arrowroot plant (Maranta arundinacea L.) radiated by gamma ray - Puspita Deswina; Luluk Prihastuti; Aziz Saputra (Jurusan Agroteknologi, 2019)
Arrowroot plants (Maranta arundinacea L.) have enormous potential to be developed as the alternative foods. Various kinds of functional food products can be processed from arrowroot tubers, because they have lower calories and IG (Glycemic Index) contents compared to the other tubers. The study aimed to determine the characteristics of the phenotype, productivity and anatomy of leaves of arrowroot plants radiated by gamma ray. The study used factorial randomized block design with 2 factors. The first factor was arrowroot accessions (Pulosari, 25 Pandeglang, Cikondang, Tamansari, and MN-1), and the second factor was radiation dose (0, 10, 20, 30, 40, 50 Gray), and those was arranged in three replications. Based on the results of the study, it found that: Pulosari accession without radiation and 30 Gray radiation required the fastest time of 12 days for shoots growth. The highest plant growth (106,88cm) was Cikondang accession with 20 Gray radiation treatment; while the shortest plant (59.61cm) was found in Cikondang accession with 30 Gray radiation dose as well. The number of productive tillers (3.0) was mostly found in Pulosari accession without radiation, conversely, the least (0.72) was found in MN-1 accession with 20 Gray radiation. For the maximum number of out-of-section tillers (1.17) on the 25 Pandeglang accession with 40 Gray radiation. The longest leaf growth (22.64 cm) and the widest (9.08 cm) were found in Cikondang accession without radiation, conversely, the shortest leaf growth (10.17 cm) and smallest (3.34 cm) was found in Cikondang accession radiated by 40 Gray. There were no changes to the number and shape of the stomata between the control plants and the radiated treatment, but there were changes in leaf color on 25 Pandeglang accession with radiation treatment 40 Gray.AbstrakTanaman Garut (Maranta arundinaceaL.) memiliki potensi besar untuk dikembangkan sebagai pangan alternatif. Berbagai macam produk pangan fungsional dapat diolah dari umbi Garut, karena memiliki kandungan IG (Index Glycemic) dan kalori lebih rendah dibandingkan umbi-umbi lainnya. Penelitian ini bertujuan untuk mengetahui karakteristik fenotipe, produktivitas dan anatomi daun tanaman Garut yang diberi perlakuan radiasi sinar gamma. Penelitian disusun menggunakan Rancangan Acak Kelompok (RAK) Faktorial dengan 2 faktor, dengan faktor pertama aksesi tanaman (Pulosari, 25 Pandeglang, Cikondang, Tamansari, dan MN-1), dan faktor kedua adalah dosis radiasi (0, 10, 20, 30, 40, 50 Gray), penelitian terdiri dari 3 ulangan. Berdasarkan hasil penelitian diketahui bahwa aksesi Pulosari tanpa radiasi dan radiasi 30 Gray memerlukan waktu keluar tunas paling cepat yaitu 12 hari. Pertumbuhan tanaman paling tinggi (106,88 cm) adalah aksesi Cikondang dengan perlakuan radiasi 20 Gray, sedangkan tanaman paling pendek (59,61 cm) juga terdapat pada aksesi Cikondang dengan dosis radiasi 30 Gray. Jumlah anakan produktif (3,0) paling banyak terdapat pada aksesi Pulosari tanpa radiasi, sebaliknya yang paling sedikit (0,72) terdapat pada aksesi MN-1 radiasi 20 Gray. Untuk jumlah anakan keluar ruas paling banyak (1,17) pada aksesi 25 Pandeglang dengan dosis radiasi 40 Gray. Pertumbuhan daun paling panjang (22,64 cm) dan paling lebar (9,08 cm) selama pengamatan terdapat pada aksesi Cikondang tanpa radiasi. Sebaliknya pertumbuhan daun paling pendek (10,17 cm) dan kecil (3,34 cm) juga terdapat pada aksesi Cikondang dan radiasi 40 Gray. Tidak terdapat perubahan terhadap jumlah dan bentuk stomata antara tanaman kontrol dengan perlakuan radiasi, akan tetapi terdapat perubahan warna daun pada aksesi 25 Pandeglang dengan perlakuan radiasi 40 Gray.